2004
DOI: 10.1086/381598
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for SporadicCampylobacterInfection in the United States: A Case‐Control Study in FoodNet Sites

Abstract: Campylobacter is a common cause of gastroenteritis in the United States. We conducted a population-based case-control study to determine risk factors for sporadic Campylobacter infection. During a 12-month study, we enrolled 1316 patients with culture-confirmed Campylobacter infections from 7 states, collecting demographic, clinical, and exposure data using a standardized questionnaire. We interviewed 1 matched control subject for each case patient. Thirteen percent of patients had traveled abroad. In multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
404
2
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(445 citation statements)
references
References 37 publications
26
404
2
13
Order By: Relevance
“…Consumption of undercooked seafood was associated with an increased risk of C. jejuni infection, as was also found in the Foodnet case-control study [14]. Although Campylobacter has been isolated from shellfish and crustaceans [36], the predominant species identified was C. lari [37].…”
Section: Y Doorduyn and Otherssupporting
confidence: 56%
See 3 more Smart Citations
“…Consumption of undercooked seafood was associated with an increased risk of C. jejuni infection, as was also found in the Foodnet case-control study [14]. Although Campylobacter has been isolated from shellfish and crustaceans [36], the predominant species identified was C. lari [37].…”
Section: Y Doorduyn and Otherssupporting
confidence: 56%
“…0) 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Contact with persons with gastroenteritis symptoms outside the household (20) 21 (20) 38 (8) 2 . 8 (1 .…”
Section: -5mentioning
confidence: 99%
See 2 more Smart Citations
“…Campylobacteriosis, salmonellosis, shigellosis, HUS, and toxoplasmosis are transmitted via multiple routes (foodborne, waterborne, person-to-person, and zoonotic transmission have all been documented) with non-water-related routes thought to be the primary mode of transmission. The fraction of cases acquired through water has not been precisely quantified, although some attempts at describing transmission sources have been made [12,[32][33][34][35][36][37][38][39]. Denno et al [33] reported that recreational water exposure was responsible for 44% of E. coli O157 infections (the primary infectious agent of HUS) and 23% of campylobacteriosis cases in children, while 17% of salmonellosis cases were associated with septic tank use and 11% with well water use, but risk factors could differ for adult cases.…”
Section: Discussionmentioning
confidence: 99%